Analisis Crack Pada Robot Exoskeleton Lower LIMB - Pamungkas, Daniel Sutopo; Fadhil Al Fadjri, Muhammad; Widiastuti, Hanifah (Journal of Applied Mechanical Engineering and Renewable Energy, 2025)
Failure due to material fatigue can be potentially fatal as it may lead to fractures without any initial detectable deformation. Factors such as high maximum load and large stress cycles accelerate the material fatigue process. In the design of a lower limb exoskeleton robot, the strength and safety of the robot are primary focuses, particularly in the Link Joint mechanism. The comfort and safety of the structure are determined by the geometry and type of material used. Analysis using Fracture Mechanics is employed to evaluate cracks in the Link Joint mechanical structure, with the calculation of the Stress Intensity Factor (SIF) value as an indicator of the stress intensity on the crack due to load. This research aims to identify critical stress and estimate the service life of the mechanism through testing using Finite Element Method-based software, specifically Solidworks 2020.